Set-Up of Bacterial Cellulose Production From the Genus Komagataeibacter and Its Use in a Gluten-Free Bakery Product as a Case Study - Vigentini, Ileana; Fabrizio, Vincenzo; Dellacà, Federico; Rossi, Sergio; Azario, Isabella; Mondin, Cristiano; Benaglia, Maurizio; Foschino, Roberto (Frontiers in Microbiology, 2019)
The use of bacterial cellulose in food systems is still limited due to production costs. Nine clones belonging to Komagataeibacter hansenii, K. nataicola, K. rhaeticus, K. swingsii and K. xylinus species were screened for cellulose productivity in growth tests with five different carbon sources and three nitrogen sources. The water-holding and rehydration capacities of the purified cellulose were determined. The structure of the polymer was investigated through NMR spectroscopy, ATR-FTIR spectroscopy and XRD analysis, and observed by SEM. Natural mutants of K. rhaeticus LMG 22126T and K swingsii LMG 22125T showed different productivity. The factors “bacterial isolate” and “nitrogen source” significantly affected the production of cellulose (p < 0.01) rather than the factor “carbon source” (p = 0.15). However, on average, the best conditions for increasing yield were found in medium containing glucose and peptone. Water-holding capacity values ranged from 10.7 to 42.3 (gwater/gcellulose) with significant differences among strains (p <0.01), while the rehydration capacity varied from 4.2 to 9.3 (gwater/gcellulose). A high crystallinity (64-80%) was detected in all samples with Iα fractions corresponding to 67-93%. The ATR-FT-IR spectra and the XRD patterns confirmed the expected structure. Bacterial cellulose made by GVP isolate of K. rhaeticus LMG 22126T, which was the strain with the highest yield, was added to a gluten-free bread formulation. Results obtained from measurements of technological parameters in dough leavening and baking trials were promising for implementation in potential novel foods.